2013
DOI: 10.1021/ic302856b
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks as Hosts for Photochromic Guest Molecules

Abstract: Several metal-organic framework compounds (MOF-5, MIL-68(Ga), MIL-68(In), MIL-53(Al)) were loaded with azobenzene (AZB), as confirmed by XRPD measurements and elemental analysis. By IR spectroscopy, it was shown that the light-induced trans/cis isomerization of AZB in these hybrid host-guest compounds is improved compared to that of solid AZB. A population of the excited cis state up to 30% has been obtained for AZB0.66@MIL-68(In). However, no light-induced trans/cis isomerization was observed for AZB0.5@MIL-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 40 publications
4
130
0
Order By: Relevance
“…By analysing the intensity of the infrared vibrational band at about 720 cm −1 , which can be assigned to trans azobenzene42, the percentage of trans azobenzene and therefore of cis azobenzene in the MOF structure was determined. This band may be assigned to the γ(CH) and τ(ring) vibration of the trans azobenzene side group, which, because of the bonding to the framework, is red shifted in comparison to the vibration band of the isolated azobenzene4344.…”
Section: Resultsmentioning
confidence: 98%
“…By analysing the intensity of the infrared vibrational band at about 720 cm −1 , which can be assigned to trans azobenzene42, the percentage of trans azobenzene and therefore of cis azobenzene in the MOF structure was determined. This band may be assigned to the γ(CH) and τ(ring) vibration of the trans azobenzene side group, which, because of the bonding to the framework, is red shifted in comparison to the vibration band of the isolated azobenzene4344.…”
Section: Resultsmentioning
confidence: 98%
“…A few years ago we started to establish MOFs as suitable hosts for the embedment of photochromic guests like azobenzenes and spiropyrans . To embed the photochromic guests we developed a gas phase procedure (see Experimental Section) .…”
Section: Resultsmentioning
confidence: 99%
“…The E / Z isomerization of azobenzene (abbreviated to AZB in the following), which is shown in Scheme , can be regarded as the prototype of photochromism. The successful embedment of AZB into the MOFs MOF‐5, MIL‐68(In), MIL‐68(Ga), MIL‐53(Al), and DMOF‐1 was already shown, and for the latter the remote‐controlled uptake and release of CO 2 was proven . It is however a severe drawback of AZB that UV light, that might interfere with the host matrix, is needed to induce the E / Z isomerization.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[34] Hermann et al performed similar studies on MOF-5, MIL-68(M) (M ¼ Ga, In), and MIL-53(Al), where it was demonstrated that photoactive guests can only induce structural changes in MOFs if the pore size of the MOF allows for it, and if there is no dense packing of the azobenzene. [35] More recently, efforts have focussed on using visible light for the capture and release of CO 2 . Hill et al have incorporated methyl red (an azobenzene derivative) into the pores of Mg-MOF-74 and MIL-53(Al), which assisted in the adsorption of CO 2 after exposure to visible light.…”
Section: Introductionmentioning
confidence: 99%